2015
DOI: 10.3832/ifor1110-007
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-release fertilizers combined with Pseudomonas fluorescens rhizobacteria inoculum improve growth in Pinus halepensis seedlings

Abstract: © iForest -Biogeosciences and Forestry IntroductionPinus halepensis is one of the most common tree species in the Mediterranean and is also frequently used for reforestation purposes (Maestre & Cortina 2004). Several studies have been carried out with the aim of improving the quality of P. halepensis seedlings obtained from nurseries (Caravaca et al. 2005). The application of chemical fertilizer treatments to forest seedlings in nurseries is the most common cultivation practice. However, it has been establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…However, under water deficit stress, reduced water uptake and curtailed transpiration result in a decrease in leaf Ca content ( Maksimović et al, 2003 ). In line with the findings of Dominguez-Nuñez et al (2014) on Pinus halepensis and Meddich et al (2015) on Phoenix dactylifera , we observed AMF- and PGPR-induced increases in root and foliar Ca contents of myrtle seedlings ( Figure 5 ). Apart from increases in Ca availability resulting from the exploitation of a larger soil volume through AMF hyphae and accelerated mineral weathering linked to PGPR secretions, the positive inoculation effect on Ca levels in myrtle seedlings may in part be due to increases in stomatal conductance and transpiration given the role of xylem sap flow in Ca mobility ( Ruiz-Lozano et al, 1995 ; Wu and Xia, 2006 ; Garg and Bhandari, 2016 ; Azizi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, under water deficit stress, reduced water uptake and curtailed transpiration result in a decrease in leaf Ca content ( Maksimović et al, 2003 ). In line with the findings of Dominguez-Nuñez et al (2014) on Pinus halepensis and Meddich et al (2015) on Phoenix dactylifera , we observed AMF- and PGPR-induced increases in root and foliar Ca contents of myrtle seedlings ( Figure 5 ). Apart from increases in Ca availability resulting from the exploitation of a larger soil volume through AMF hyphae and accelerated mineral weathering linked to PGPR secretions, the positive inoculation effect on Ca levels in myrtle seedlings may in part be due to increases in stomatal conductance and transpiration given the role of xylem sap flow in Ca mobility ( Ruiz-Lozano et al, 1995 ; Wu and Xia, 2006 ; Garg and Bhandari, 2016 ; Azizi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has been carried with the same bacterium, but different plant species. Dominguez-Nuñez et al (2015) noticed that Pinus halepensis seedlings inoculated with Pseudomonas fluorescens had a 26% wider root-colar diameter. Shoot dry weight was also greater in inoculated plants, but height and root dry weight were not influenced by inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Estudios sobre la aplicación de rizobacterias y fertilizantes sintéticos han reportado un incremento en el crecimiento de las plantas, debido a una mayor capacidad de absorción de los nutrimentos (Dominguez-Nuñez et al, 2015;Paungfoo-Lonhienne et al, 2019), promovida principalmente por el aumento de las poblaciones rizobacterianas (Tahir et al, 2018). Al respecto Naseri y Mirzaei (2010), reportan que la aplicación de Azotobacter sp.…”
Section: Introductionunclassified